Answer:
h = 2
Step-by-step explanation:
6x + 18 = h (3x + 9)
To get the value of h, we simply need to make h subject of the formula;
To make h subject of the formula, we simply divide both-side of the equation by (3x + 9)
= ![\frac{h(3x + 9)}{(3x + 9)}](https://tex.z-dn.net/?f=%5Cfrac%7Bh%283x%20%2B%209%29%7D%7B%283x%20%2B%209%29%7D)
(On the right hand side of the equation (3x+2) will cancel out (3x+2) leaving us with h)
= h
h =
----------------(1)
We want to make the numerator and denominator look the same so that we can cancel out, at the numerator, we can factor out 2 from 6x + 18
i.e 6x + 18 = 2 ( 3x + 9)
So we can replace 6x + 18 by 2(3x + 9) in equation (1)
h = ![\frac{2 (3x + 9)}{(3x +9)}](https://tex.z-dn.net/?f=%5Cfrac%7B2%20%283x%20%2B%209%29%7D%7B%283x%20%2B9%29%7D)
( on the right hand side of the equation, (3x + 9) will cancel out (3x + 9) leaving us with just 2)
<em>h = 2</em>
We can plug in our h =2 in the initial equation
6x + 18 = 2(3x + 9)
6x + 18 = 6x + 18
This equation has an infinite number of solutions.
Therefore the value of constant h in the equation that can make the equation have an infinite number of solutions is 2